2014
DOI: 10.3109/01443615.2014.919577
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis of 6,142 amniocentesis cases: A 6-year single centre experience

Abstract: The aim of our study was to evaluate the incidences and chromosomal abnormality detection rates of various indications for genetic amniocentesis. We retrospectively analysed 6,142 amniocentesis cases performed in a single centre between January 2007 and April 2013. We assessed the indications for prenatal diagnosis, fetal karyotypes, maternal ages, fetal ultrasound findings and maternal serum screening results. The most common indication for genetic amniocentesis was an abnormal maternal serum-screening test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(42 reference statements)
0
6
1
Order By: Relevance
“…We found that the most prominent indicator for amniocentesis was the maternal age. This is in accordance with the findings of Yang et al (7), but in contrast to the finding of some other authors who found that the most prominent indicator for amniocentesis was an abnormal maternal serum-screening test or abnormal ultrasound findings (6,8,9).…”
Section: Discussion:-contrasting
confidence: 57%
See 1 more Smart Citation
“…We found that the most prominent indicator for amniocentesis was the maternal age. This is in accordance with the findings of Yang et al (7), but in contrast to the finding of some other authors who found that the most prominent indicator for amniocentesis was an abnormal maternal serum-screening test or abnormal ultrasound findings (6,8,9).…”
Section: Discussion:-contrasting
confidence: 57%
“…In our study we paid attentionto the women who were referred for amniocentesis. Indications for amniocentesis we divided into the six groups; similar divisions were also done in other studies (5,6). We found that the most prominent indicator for amniocentesis was the maternal age.…”
Section: Discussion:-mentioning
confidence: 93%
“…Indications for amniocentesis include advanced maternal age, abnormal serum hormone levels, family history of chromosomal abnormalities, and abnormal fetal ultrasound findings [8][9][10][11]. The indications for amniocentesis have evolved over the years [12]. Advanced maternal age has been the primary indicator for amniocentesis, but new biochemical serum tests are now widely used for the detection of chromosomal abnormalities [8].…”
Section: Introductionmentioning
confidence: 99%
“…Invasive procedures such as amniocentesis and chorionic villus sampling (CVS) have been the most common and widely used (Simpson 2012), while non-invasive prenatal testing (NIPT) or diagnosis (NIPD) has been more recently introduced for use in some prenatal testing situations (Hill, Barrett et al 2012). Clinical indications for prenatal testing include advanced maternal age (35 and older), family history of an inherited disorder, indications of fetal abnormality, such as an abnormal ultrasound examination (Lo, Cori D et al 2014) or high risk prenatal screening result (Ekin, Gezer et al 2014). The recognised advantages of invasive prenatal diagnostic procedures, such as obtaining definitive diagnostic results, are balanced against the associated health risk to the fetus, specifically, pregnancy loss rates following amniocentesis and CVS are typically around 1% (Mujezinovic and Alfirevic 2012).…”
Section: Introductionmentioning
confidence: 99%